INTEGRATED NUTRIENT AND PEST MANAGEMENT (INM + IPM) APPROACHES FOR REDUCING CHEMICAL INPUTS IN PADDY FIELDS OF EASTERN UTTAR PRADESH - Akriti Vigya (International Educational Journal of Science and Engineering, 2025)
The intensification of rice cultivation in Eastern Uttar Pradesh has historically relied on heavy chemical inputs, leading to ecological degradation and diminishing economic returns for smallholder farmers. This study evaluates the synergistic impact of Integrated Nutrient Management (INM) and Integrated Pest Management (IPM) on paddy (Oryza sativa) during the 2023-2024 cropping cycle. Utilizing a combination of bio-fertilizers, neem-based pesticides, and pheromone traps alongside reduced chemical doses, the research demonstrates a 25% reduction in synthetic fertilizer dependency and a 40% reduction in pesticide expenditure. Results indicate that the INM+IPM approach maintains yield parity with conventional systems while significantly enhancing soil microbial health and farmer profitability.